Pengurangan Penggunaan Plastik Pada UMKM Perkampungan Wisata Budaya Betawi Setu Babakan Jakarta - Haswan Yunaz; Ahmad Nurdin Hasibuan; Dodi Wahab; Reny Andriyanty (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
This program objection for assisting the government's efforts to reduce the plastics using in Indonesia, especially in South Jakarta. The expected benefit of the activity is the increasing of enviromental care insight by suppressing the plastic wrap using for small business unit in the Betawi Cultural Tourism Setu Babakan Village South Jakarta. The activity was counseling and discussion. The target audience was small and micro business units. The programme results are 92 percent of participants will suppress the use of plastic as a wrapper and 8 percent still do not have the desire to suppress the use of plastic wrap. 92 percent of them will try to apply the green marketing concept and there are still 8 percent who do not want to apply this concept. Ninety seven percent of participants stated that this activity provided benefits and increased understanding of reducing plastics using and the concept of green marketing.